Empresa de alquiler de muebles y accesorios para bebes - Navas Recalde, María Andrea (2009)
The company AGUSITOS, is bom by knowing that the price in baby products is very high. A1though they have short usage, do to the fast growth in children, also families with the pass of time have less children. And because of this, inheritance is something that is getting lost in time. The situation in which the company is lactated, in the industry as in the sector is favorable, the services within the GNP are in average around 25%, in macro environment, we can observe a decreasing birth rate with an average of 3.3% and a death rate with an average decreasing of 1'1.32%, positive factors for the company. In legal and political issues, there's an advantage because of the raise in value of imports, so this will cause an increase in the price on selected Products, with a microenvironment study, this business counts with a lot of suppliers, no direct competition, high power and purchase capacity on buyers, which counteracts the different a1ternatives, and the easy entry of competition to the market. The market research concluded that the target in marketing segmentation is parents between 18 to 40 years old. Who, by the high cost in products prefer to rent them. Qualitative and Quantitative research gives favorable results to the company. A mission is created to move the company as a horizontal organization, as well as a vision for the next nave years, structured within the values of responsibility, fidelity, commitment, honesty, pro activity and good service; and also the SWOT strategies are created with the purpose of achieving objectives for the growth of the company. A marketing plan is also created, in which is defined a level! Of demand of 98.370 born babies per year. For strategic marketing, differentiation of products and services is given. As well as Iow prices, and for tactical marketing; newly products, loyalty promotions to attract customers, situated in strategic locations. We performed a financial assessment, taking a chance rate of 13.5%, cash f10ws obtaining net current value scenario leveraged of $662.663 and non-leveraged of $650895, as well as a IRR leveraged of 160% Y non leveraged of 118%; in both pessimistic and optimistic scenarios, there are positive results Designs a contingency plan for different situations, presenting solutions for each and every one other.